Population - declension or explosion?: A case study - Cabalag, Adelaida (Animo Repository, 1979)
In the present case, the School Administrative Board had to make a decision especially that enrollment date was getting nearer. Would Sta. Gabriela Academy allow the current situation to exist until it would be too late to change the course of action or should they venture to accept boys in the High School Department and try every possible means to remedy the consequences?